Medida socioeducativa de internação e ressocialização: análise das contribuições das práticas pedagógicas no centro socioeducativo de internação, à luz do pensamento Freireano - FURTADO, Angélica de Oliveira (UNIFAP – Universidade Federal do Amapá, 2022)
The socio-educational measure of hospitalization, provided for by the Statute of the Child and Adolescent - ECA and reaffirmed by the National System of Socio-Educational Service - SINASE, is a measure of deprivation of liberty, holding the adolescent legally responsible for the practice of an infraction, which implies his hospitalization. . It establishes the mandatory schooling during its fulfillment, demanding that the articulation between different public policies be carried out in parallel, with a view to disinternation. Given the above, the research originated from the following problem: from the perspective of Freire's contributions, how pedagogical practices, such as socio-educational measures for hospitalization, developed at the Socio-educational Center for Hospitalization - CESEIN contribute to the re-socialization of adolescent authors offense in the State of Amapá? So, it had as general objective to analyze the pedagogical practices, such as socio-educational measures of detention, at the Socio-educational Center of Detention - CESEIN, and his contributions to the re-socialization of adolescents who committed an infraction in the State of Amapá, taking Freirean contributions as a guideline, showing the construction of education as a practice of freedom, guided by in dialogue, autonomy, reflection and criticality. The methodological strategy used was the case study, with a qualitative approach. The research was carried out at the school installed at the Socio-Educational Center for Detention in Macapá/Amapá, with eight teenagers and nine educators, adopting participant observation and semi-structured interviews for data collection. The observation took place specifically in the classrooms of the educators in the classes of Elementary Education II, in two classes of 3rd Stage and a class of 4th Stage of the Youth, in Adult Education modality. Data processing was performed based on content analysis. Among the main results, the following stand out: the teenage who commits offenses is marked as a negative person to society and the educational process provided by the Child and Adolescent Statute, as an alternative to life changing, is still dissonant from its purpose, due to deficiencies in teacher training, despite that, educators put dedication.